Changes in the effect of corporate tax avoidance on the cost of debt over the past 25 years - Lee, Sungsil (Pacific Accounting Review, 2022)
Purpose: This study aims to examine how the effect of corporate tax avoidance on the cost of debt has changed in the period 1993–2017. Although it is known that tax avoidance has significantly increased during this period (Dyreng et al., 2017), little evidence exists on how this change alters the effect of tax avoidance on the cost of debt. This study investigates how changes in tax avoidance modify the association between tax avoidance and the cost of debt. Design/methodology/approach: By using a comprehensive sample of 15,825 loan facilities issued to US public firms in the period 1993–2017, this study tests the time-series changes in the association between tax avoidance and the cost of debt. Findings: This study finds that a positive association between tax avoidance and the cost of debt has been declined over the past 25 years. Accordingly, tax avoidance in general no longer increases the loan spread after the enactment of domestic production activities deduction. However, the risker end of tax avoidance does still increase the loan spread. Originality/value: This study spotlights the time-series changes in the effect of corporate tax avoidance on the cost of debt, showing how lenders perception on corporate tax avoidance has altered in accordance with changes in corporate tax practice.
Keywords: Cost of debt; Tax; Tax avoidance; Tax risk; Time trend